Innovative IT Solutions in The Field of External Relations In Collectibility of Budget Receivables on The Example of Common Courts of The West Pomeranian Voivodeship in Poland - Rafal MAZUR (Communications of International Proceedings, 2021)
The article analyzes the functioning of a modern IT solution in budgetary units, and more precisely in common courts located in the West Pomeranian Voivodeship in Poland. The focus was on the effects that were achieved after the implementation of the application for recording court receivables, made in the three-layer technology. The tested solution, along with the necessary services, is installed at the Appellate Court in Szczecin and is associated with many external applications such as: Integrated Accounting and Human Resources System (ZSRK), Economic Information Bureaus, Mail Service System for Return Acknowledgment of Receipt and Electronic Acknowledgment Receipt, central printing system, Report Integrator of the Ministry of Justice, and departmental adjudication systems in each court.
Keywords: Innovation; development; common judiciary